Subprime mortgage pricing: The impact of race, ethnicity, and gender on the cost of borrowing - Andrew Haughwout; Christopher Mayer; Joseph Tracy (Federal Reserve Bank of New York, 2009)
Some observers have argued that minority borrowers and neighborhoods were targeted for expensive credit in 2004-06, the peak period for subprime lending. To investigate this claim, we take advantage of a new data set that merges demographic information on subprime borrowers with information on the mortgages they took out. In a sample of more than 75,000 adjustable-rate mortgages, we find no evidence of adverse pricing by race, ethnicity, or gender in either the initial rate or the reset margin. Indeed, if any pricing differential exists, minority borrowers appear to pay slightly lower rates, as do those borrowers in Zip codes with a larger percentage of black or Hispanic residents or a higher unemployment rate. Mortgage rates are also lower in locations that previously had higher rates of house price appreciation. These results suggest some economies of scale in subprime lending. Yet there are important caveats: we are unable to measure points and fees at loan origination, and the data do not indicate whether borrowers might have qualified for less expensive conforming mortgages.
Keywords: G21; D40; 330; Subprime; mortgages; HMDA; Subprime-Hypothek; Zins; Ethnische Diskriminierung; Geschlechterdiskriminierung; USA